Mycobacterium tuberculosis EsxO (Rv2346c) promotes bacillary survival by inducing oxidative stress mediated genomic instability in macrophages. (January 2016) - Mohanty, Soumitra; Dal Molin, Michael; Ganguli, Geetanjali; Padhi, Avinash; Jena, Prajna; Selchow, Petra; Sengupta, Srabasti; Meuli, Michael; Sander, Peter; Sonawane, Avinash
Summary: Mycobacterium tuberculosis ( Mtb ) survives inside the macrophages by modulating the host immune responses in its favor. The 6-kDa early secretory antigenic target (ESAT-6; esxA) of Mtb is known as a potent virulence and T-cell antigenic determinant. At least 23 such ESAT-6 family proteins are encoded in the genome of Mtb ; however, the function of many of them is still unknown. We herein report that ectopic expression of Mtb Rv2346c (esxO), a member of ESAT-6 family proteins, in non-pathogenic Mycobacterium smegmatis strain ( Msm Rv2346c) aids host cell invasion and intracellular bacillary persistence. Further mechanistic studies revealed that Msm Rv2346c infection abated macrophage immunity by inducing host cell death and genomic instability as evident from the appearance of several DNA damage markers. We further report that the induction of genomic instability in infected cells was due to increase in the hosts oxidative stress responses. Msm Rv2346c infection was also found to induce autophagy and modulate the immune function of macrophages. In contrast, blockade of Rv2346c induced oxidative stress by treatment with ROS inhibitor N-acetyl-L-cysteine prevented the host cell death, autophagy induction and genomic instability in infected macrophages. Conversely, Mtb ΔRv2346c mutant did not show any difference in intracellular survival and oxidative stress responses. We envision that Mtb ESAT-6 family protein Rv2346c dampens antibacterial effector functions namely by inducing oxidative stress mediated genomic instability in infected macrophages, while loss of Rv2346c gene function may be compensated by other redundant ESAT-6 family proteins. Thus EsxO plays an important role in mycobacterial pathogenesis in the context of innate immunity.